Yield strength anomaly and dynamic strain ageing behaviour of recently developed advanced ultra-supercritical boiler grade wrought Ni-based superalloy IN 740H. (4th May 2019) - Singh, R. K.; Sahu, J. K.
ABSTRACT: The yield strength anomaly (YSA) and dynamic strain ageing (DSA) behaviour of advanced ultra-supercritical boiler grade wrought nickel-based superalloy IN 740H is studied by conducting tensile tests in temperature range 28–930°C and by employing strain rates 1 × 10 −2, 1 × 10 −3, 1 × 10 −4 and 1 × 10 −5  s −1 followed by extensive electron microscopic examination. Increase in yield strength accompanied by impairment of ductility indicates that YSA exists in alloy IN 740H in temperature range of 650–760°C. The electron microscopic observation confirms that YSA is due to pinning of dislocations by γ ′ precipitates and shearing of γ ′ precipitates in IN 740H. DSA is observed in the temperature range of 200–500°C and is predominant at 300°C. The nature of serrated plastic flow due to DSA is dependent on the temperature and strain rate.